Sports participation and radiographic findings of adolescents treated nonoperatively for displaced clavicle fractures - Robinson, Luke; Gargoum, Riyad; Auer, Ron; Nyland, John; Chan, Gilbert (Injury, 2015)
There is a relative paucity of high-level evidence that guides the treatment of displaced midshaft clavicle fractures in adolescents. Some use overhead sports or significant shortening as relative indications for surgical treatment, while others rarely consider operative intervention for these patients. The purpose of this study is to determine the effect of overhead sports participation and fracture shortening on subjective and objective outcomes after nonoperative treatment of displaced midshaft clavicle fractures in those aged 10–17 years. Using a radiographic database, adolescents with displaced clavicle fractures were identified and contacted over the phone. These subjects were invited to take part in the study in return for compensation. Radiographic measurements of dedicated clavicle films around the time of injury were performed, and a custom survey aimed at elucidating participation in overhead or contact sports was given. The Nottingham Clavicle Score (NCS) and the Constant Shoulder Score were obtained for each patient to provide both subjective and objective outcome data. Statistical Package for Social Science (SPSS) software (version 22, IBM) was used to compare radiographic and sports data to the outcome measures. Gender, age at the time of fracture, time since fracture, relative and absolute radiographic shortening, and hand dominance were all not significantly correlated with subjective or objective outcomes. Five patients (23%) reported not feeling happy with the appearance of their shoulder at the beach or at the pool. This group had statistically lower NCS results. Eleven of 22 participated in ≥6 months per year of overhead or contact sports; they did not have worse subjective or objective outcomes. Fracture shortening and sports participation do not have a significant impact in adolescents on outcomes after displaced midshaft clavicle fracture.